An interpretative phenomenological analysis of post traumatic growth in adults bereaved by suicide - Smith, Angela (2010)
This thesis explored the experiences of post-traumatic growth in adults bereaved by suicide. Past literature into posttraumatic growth, posttraumatic growth in bereavement and bereavement by suicide is examined to rationalise the current research. There is critique of the methodologies used in the past literature.